Photoacclimation state determines the photobehaviour of motile microalgae: the case of a benthic diatom - Ezequiel, João
High productivity in intertidal microphytobenthic communities is achieved despite exposure to extreme and dynamic conditions (e.g. light, salinity, temperature). As an adaptation to this hostile environment, most of the microalgae species inhabiting fine-sediment habitats are motile, being able to migrate vertically within the uppermost layers of the sediment and actively regulating their exposure to light. In this work we tested the hypothesis that the migratory photobehaviour of benthic diatoms, the dominant group in microphytobenthic assemblages, is conditioned by their photophysiological state (i.e. photoacclimation). Unialgal cultures of themotile diatom Navicula cf. recenswere grown under contrasting light regimes (20 and 300 μmol quantam−2 s−1) to induce different photoacclimation states. The migratory response to light was characterized by studying the distribution of motile cells along a light gradient (photoaccumulation curve), using a custom-build photoaccumulation chamber. The photoaccumulation curves were constructed by measuring the accumulation of cells along the light gradient using a light transmission index. The variation of the photophysiological state of the cells along the light gradient was measured using Pulse Amplitude Modulation (PAM) fluorometry (maximum quantum yield and light response curves of the relative electron transport rate of photosystem II). The results showed clearly different photoaccumulation curves for low and high-light acclimated cells. Although in both cases, cells avoided extreme lowand high light levels,maximumcell accumulation was reached at markedly different light intensities depending on growth light conditions and resulting photoacclimation state: 72 and 104 μmol quanta m−2 s−1 for the low and high light-acclimated cells, respectively. Strong relationships were found between photophysiological parameters characterizing photoacclimation or susceptibility to photoinhibition and migratory light response, supporting that this diatom uses motility to select the optimal light exposure according to its photophysiological preferences.